TRPC4 ion channel regulations by small-molecular inhibitors and calmodulin. (May 2021) - Zhang, Jingli; Li, Zongli
Abstract: TRPC4 ion channel was reported to be regulated by small molecular inhibitors and calmodulin. We discuss these findings in the context of other members of TRPC subfamily modulated by different stimulants.